A nomogram model for prognosis of acute ischemic stroke treated with recombinant tissue-type plasminogen activator - Bai, Song; Liu, Yan; Zhang, Chenggang; Ren, Yuan (Frontiers in Neurology, 2025)
ObjectiveThe primary objective of this study was to systematically assess the prognostic utility of neutrophil-derived inflammatory indices—specifically the neutrophil-to-lymphocyte ratio (NLR) and systemic inflammation response index (SIRI)—and subsequently develop a predictive model for thrombolysis outcomes through the integration of these hematological biomarkers with clinical parameters, including acute-phase neurological severity (as quantified by baseline National Institutes of Health Stroke Scale [NIHSS] scores) and therapeutic timeliness (door-to-needle time, DNT) in acute ischemic stroke patients receiving recombinant tissue plasminogen activator (rt-PA) therapy.MethodsThis retrospective cohort study analyzed consecutive patients with AIS who received intravenous thrombolysis with rt-PA at the First People’s Hospital of Chuzhou in Anhui Province, China, between January 2021 and July 2023. Peripheral blood samples were collected within 24 h of admission to evaluate the NLR and SIRI. Univariate and multivariate logistic regression models were employed to assess the associations of NLR, SIRI, NIHSS score at admission, and DNT with short-term prognosis after intravenous thrombolysis for acute cerebral infarction. Receiver operating characteristic (ROC) curve analysis was conducted to assess the predictive capacity of the NLR, SIRI, NIHSS scores, DNT for clinical outcomes in AIS patients.ResultsA total of 232 AIS patients treated with rt-PA IVT completed the 3-month follow-up. Multivariate logistic regression confirmed NIHSS score, DNT time, NLR, and SIRI as independently associated with worse prognosis (all p < 0.01). ROC analysis confirmed individual AUCs of 0.779 for NIHSS, 0.737 for NLR, 0.701 for SIRI, and 0.732 for DNT. The nomogram integrating NIHSS score, SIRI, NLR, and DNT was established, yielding an AUC of 0.885, and showing robust predictive accuracy with an internally validated AUC of 0.887 and externally validated AUC of 0.882.ConclusionThis study affirms that specific inflammatory markers like NLR and SIRI, alongside initial stroke severity and treatment timeliness, emerge as significant prognosis predictors in thrombolysis-treated stroke patients. By amalgamating these biomarkers, the proposed nomogram empowers clinicians to foresee and manage patient outcomes more effectively.